La gamificación como metodología activa para el fortalecimiento del proceso de enseñanza en el área de estudios sociales de los estudiantes de 4to año de educación básica en la unidad educativa La Maná. - Pazmiño Cano , Daniel Alejandro (2025)
The general objective of this research was to propose gamification as an active methodology to strengthen the teaching of Social Studies among 4th-year Basic Education students at the "La Maná" Educational Unit. The study was conducted using a quantitative approach, with a descriptive design. A sample of 102 4th-year Basic Education students was selected. Analytical methods and surveys validated by experts were used, as well as statistical tools for the analysis of results. The results revealed that the institution predominantly uses traditional methodologies, with limited inclusion of technological resources, which limits student motivation and active learning. Based on this diagnosis, a proposal was developed based on five teaching strategies based on gamification. These strategies were validated by specialists and users, proving to be viable, feasible, and effective in their partial implementation. This helped us to conduct and gather more information where the use of electronic devices in the classroom is very limited. In conclusion, it was evident that the implementation of gamification enhances the teaching-learning process, generating greater student interest, participation, and understanding of the content. It is recommended that strategies be applied systematically and appropriately to achieve the proposed educational objectives and overcome the shortcomings identified in the use of active methodologies. This study provides an innovative tool that can significantly improve the teaching of Social Studies at the General Basic Education level.